(untitled) (Docentes 2.0 Journal, 2019)
This article demonstrates the adaptation of Solé’s theory through a series of strategies, still in validation, that are proposed to students of basic education (sixth grade) in Manuel J del Castillo Educational Institution in the department of Magdalena, Colombia. This, in order to develop in the mentioned students, the levels of criticality, because they are in a propitious stage to begin to understand and react to the different realities to which they can be exposed on a daily basis. However, learning activities are incorporated that simultaneously stimulate interest in reading and writing as co-dependent processes. The methodological exercise is supported in the moments and strategies of reading that Isabel Solé enunciates as necessary elements to develop recurrent, competent and critical reading processes. Therefore, the importance of a selection of different types of texts that are relevant to the development of autonomous thinking within the teaching-learning processes and the social context. These reflections arise from the comparative study of theories and reading strategies in addition to the shortcomings in the critical competence of texts and situations observed in the classroom.